2004
DOI: 10.1111/j.1365-2672.2004.02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversities and similarities in PFGE profiles of Campylobacter jejuni isolated from migrating birds and humans

Abstract: Aims: To genetically sub-type Campylobacter jejuni strains isolated from migratory birds, and to compare these with clinical strains collected in the same area and corresponding time period, with the aim to increase our knowledge on sub-types occurring among wild birds and their possible impact on human disease. Methods and Results: We sub-typed C. jejuni strains from migrating birds (n ¼ 89) and humans (n ¼ 47), using macrorestriction profiling by pulsed-field gel electrophoresis. Isolates from migrant birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 22 publications
4
67
1
2
Order By: Relevance
“…Furthermore, ten out of the twelve poultry C. jejuni strains tested were able to colonize chicken intestines permanently, while two strains colonized the intestines either poorly or not at all. Other reports contradict local transmission, which may support the hypothesis of association between different subtypes of C. jejuni and certain species or guilds of hosts (Broman et al 2004).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, ten out of the twelve poultry C. jejuni strains tested were able to colonize chicken intestines permanently, while two strains colonized the intestines either poorly or not at all. Other reports contradict local transmission, which may support the hypothesis of association between different subtypes of C. jejuni and certain species or guilds of hosts (Broman et al 2004).…”
Section: Resultsmentioning
confidence: 61%
“…Broman et al (2002) found only a few strains from black-headed gull that had genotypic profiles identical to those from human strains. Broman et al (2004) subtyped C. jejuni strains from migrant birds by pulsed-field gel electrophoresis. Isolates often exhibited subtypes with higher levels of similarity to isolates from birds of the same species or feeding guild, than to isolates from other groups of birds.…”
mentioning
confidence: 99%
“…Wild birds are known to carry and transmit over 40 diseases to humans and livestock (13,24,34,35,36,49). Recent studies have also highlighted wild birds as sources of pathogens associated with human disease (5,9,22,50). Some species of wild birds, such as European starlings, house sparrows, and rock doves, are adapted to urbanized settings and are attracted to livestock facilities (13,14,25,36).…”
mentioning
confidence: 99%
“…Therefore, avian wildlife are a potential source for spreading infectious diseases to livestock year round. Escherichia coli O157:H7, Salmonella, Listeria, and Campylobacter are among pathogens that have been recognized as being carried by avian wildlife and are potentially pathogenic to humans and livestock (5,13,35,43,49,50). Mycobacterium avium subsp.…”
mentioning
confidence: 99%
“…23 As for avian influenzas, wild birds are the natural vertebrate reservoirs of Campylobacter, and they can serve as vectors for transmission to other vertebrates. [50][51][52][53][54][55][56] Campylobacter moves among avian host species, both domesticated 57 and wild, [58][59][60] and the exchange of Campylobacter between broiler flocks and wild avians can occur in both directions. 61 There are several pathways for Campylobacter colonization of broiler flocks including in ovo vertical transmission, carryover from previous flocks, horizontal transfer from other animals (wild or domestic), and contaminated feed and water.…”
Section: Environmental Pathwaysmentioning
confidence: 99%